Substâncias antifúngicas de Xylaria sp., um fungo endofítico isolado de Palicourea marcgravii (Rubiaceae) - Cafêu, Mariana Carrara [UNESP]; Silva, Geraldo H. [UNESP]; Teles, Helder L. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Araújo, Angela Regina [UNESP]; Young, Maria Cláudia M.; Pfenning, Ludwig H. (Sociedade Brasileira de Química, 2005)
Five compounds, 2-hexyl-3-methyl-butanodioic acid (1), cytochalasin D (2), 7-dechlorogriseofulvin (3), cytochalasin B (4) and griseofulvin (5), have been isolated from the endophytic fungus Xylaria sp., and their structures were elucidated on the basis of spectroscopic data. In the bioautography assay against Cladosporium cladosporioides and Cladosporium sphaerospermum, compounds 1 and 2 were found to be active while compounds 3, 4 and 5 did not show antifungal activity.
Antifungal compounds of Xylaria sp., an endophytic fungus isolated from Palicourea marcgravii (Rubiaceae)
Keywords: endophytic fungus; Xylaria sp.; antifungal compounds